3D biodegradable scaffolds of polycaprolactone with silicate-containing hydroxyapatite microparticles for bone tissue engineering: high-resolution tomography and in vitro study - Shkarina S. N. Svetlana Nikolaevna; Shkarin R. Roman; Weinhardt V. Venera; Melnik E. Elizaveta; Vacun G. Gabriele; Kluger P. J. Petra Juliane; Loza K. Kateryna; Epple M. Matthias; Ivlev S. I. Sergei; Baumbach T. Tilo; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich (2018, 2018)
Title screen